ENGLISH TEACHERS’ MASTERY OF THE ENGLISH ASPIRATION AND STRESS RULES - Arina Isti'anah (Master Program in Linguistics, Diponegoro University, 2013)
This paper tries to observe the English teachers’ awareness and representation of the English aspiration and stress rules. The research purposes to find out whether or not the teachers are aware of the English aspiration and stress rules, and to find out how the teachers represent the English aspiration and stress rules. Based on the analysis, it can be concluded that the teachers’ awareness of the English aspiration and stress rules is very low. It is indicated with the percentage which equals to 44% and 48% for English aspiration and stress rules. In representing the English aspiration and stress rules, the teachers face the problems in producing aspiration in the pronunciation, placing the right stress and pronouncing three and four X in the coda position. There are two reasons affecting the teachers’ awareness of the English aspiration and stress rules namely exposure and L1 influence. Artikel ini bertujuan untuk meneliti kesadaran dan representasi aturan aspirasi dan tekanan oleh guru bahasa Inggris. Penelitian ini bertujuan untuk menjelaskan apakah guru bahasa Inggris mempunyai kesadaran atas aturan aspirasi dan tekanan dalam bahasa Inggris, dan untuk menunjukkan bagaimana guru Bahasa Inggris mewujudkan aturan aspirasi dan tekanan dalam pelafalan mereka. Berdasarkan analisis yang dilakukan, dapat disimpulkan bahwa kesadaran guru Bahasa Inggris atas aturan aspirasi dan tekanan dalam Bahasa Inggris masih sangat rendah. Hal tersebut ditunjukkan oleh rendahnya prosentase dalam perwujudan aturan aspirasi dan tekanan: 44% dan 48%. Dalam mewujudkan aturan aspirasi dan tekanan, guru Bahasa Inggris menemui masalah dalam menghasilkan aspirasi dalam pelafalan, meletakkan tekanan pada suku kata yang tepat dan pada posisi X yang berada pada posisi ketiga atau keempat. Terdapat dua alasan yang memengaruhi kesadaran partisipan atas aturan aspirasi dan tekanan, yaitu pajanan dan pengaruh bahasa pertama.